2020
DOI: 10.1016/s1473-3099(19)30554-7
|View full text |Cite
|
Sign up to set email alerts
|

Implications for annual retesting after a test-and-not-treat strategy for onchocerciasis elimination in areas co-endemic with Loa loa infection: an observational cohort study

Abstract: Summary Background A test-and-not-treat (TaNT) strategy has been developed to prevent people with high concentrations of circulating Loa loa microfilariae (>20 000 microfilariae per mL) developing serious adverse events after ivermectin treatment during mass drug administration to eliminate onchocerciasis. An important question related to cost and programmatic issues is whether annual retesting is required for everyone. We therefore aimed to investigate chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 20 publications
(27 reference statements)
0
20
0
Order By: Relevance
“…In the second round, participation was higher and varied between 60.5% and 78% of the total population. [8] Another TaNT campaign conducted in 2017-2018 in the neighboring Soa health district and involving local health personnel and community volunteers showed an overall participation of approximately 66% in rural settings. [21] Urban and semi-urban areas show consistently lower rates of participation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the second round, participation was higher and varied between 60.5% and 78% of the total population. [8] Another TaNT campaign conducted in 2017-2018 in the neighboring Soa health district and involving local health personnel and community volunteers showed an overall participation of approximately 66% in rural settings. [21] Urban and semi-urban areas show consistently lower rates of participation.…”
Section: Discussionmentioning
confidence: 99%
“…However, observations from the second TaNT round in Okola showed that the exclusion dropped from 2.1% to 1.5% within 18-months. [8] In a sensitivity analysis, we explored the impact of a decreasing exclusion rate. To match the observed change, we assumed an exponential drop (rate: 0.22 per year) in the first 10 TaNT rounds and no exclusion due to high loiasis MFD in the following rounds.…”
Section: Test-and-not-treat Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…In The Lancet Infectious Diseases, Sébastian Pion and colleagues 8 compared microfilarial counts between two MDA campaigns that were run 18 months apart, to evaluate the necessity of obtaining microfilarial counts from the same patient before each MDA. Their results showed that, of the 6983 individuals for whom complete data were available, more than 99•9% of those with a safe L loa microfilarial count who were treated with ivermectin in 2015 had a L loa microfilarial density below the threshold associated with serious adverse events on repeat testing 18 months later.…”
Section: Test-and-not-treat: Importance For Mass Drug Administrationmentioning
confidence: 99%
“…Notably, HIV serostatus of the index patient, or their household contacts, was not included in the risk score, owing to the very low prevalence (0•2%) of HIV in Peru. 8 We cannot assume the risk score will perform as well in settings with higher HIV prevalence, because HIV might affect the risk score in unexpected ways. However, in settings where many households affected by tuberculosis are also affected by HIV, the score could still be useful to better prioritise the highest-risk households and ensure that households that could benefit the most from contact investigations are reached.…”
Section: Test-and-not-treat: Importance For Mass Drug Administrationmentioning
confidence: 99%